Reaction Mechanism Analysis of a Li-O2 Battery: Structure of Electrode/Electrolyte Interface Probed Via Soft-x-Ray Absorption Spectroscopy, Hard x-Ray Photoelectron Spectroscopy, and in-Situ Hard x-Ray Diffraction. (20th November 2015) - Yogi, Chihiro; Kamiguchi, Kazuhiro; Takao, Naoki; Watanabe, Takeshi; Kubobuchi, Kei; Matsumoto, Masashi; Ohwaki, Tsukuru; Imai, Hideto
Abstract : We investigated the electrode/electrolyte interphase structure using synchrotron radiation based techniques, namely in-situ and time resolvedhard X-ray diffraction (XRD), hard X-ray photoelectron spectroscopy (HAXPES) and soft X-ray absorption fine structure spectroscopy (SXAFS). The formation and dissolution of Li2 O2 upon the discharge/charge cycle were monitored by in-situ XRD, and the structure and chemical compositions at the electrode/electrolyte interphase were analyzed by HAXPES and SXAFS. In the XRD measurements, we found the Li2 O2 formation during discharge and the rapid Li2 O2 dissolution in the charge reaction. The combination of HAXPES and SXAFS analyses revealed that a large number of side products such as carbonates, C-F compounds, LiF, sulfones, and Li2 O were generated after the discharge reaction. Furthermore, these side products were partially decomposed and/or oxidized in the charge stage. We systematically summarized the results in relation with the charge/discharge operation.